PENINGKATAN KEMAMPUAN KOSAKATA BAHASA ENDE MELALUI METODE KARYAWISATA PADA ANAK USIA DINI (5-6 Tahun) DI TK PAULUS VI DETUSOKO - Ero, Martha Karolina; Mohammad Ramli Akbar; Rina Wijayanti (Al-ATHFAL: Jurnal Pendidikan Anak, 2025)
Vocabulary is a collection of words used in a language to convey meanings, ideas and feelings. Vocabulary can also be interpreted as a treasure trove of words that a person has. This research aims to improve the vocabulary ability of the Ende language through the field trip method. The type of research used is the class roomaction research approach. This research method consists of planning, action, observation, and reflection.data is collected through several methods of vocabulary tests, classroom observations, and teacher interviews. Qualitative data analysis is used to determine the results of the research obtained. Based on the results of the research and discussion conducted by the researcher, it will be concluded that the activity of pronouncing vocabulary in the Ende language using the field trip method can improve the vocabulary ability of children of Paul VI Detusoko Kindergarten is stated that children who get three and four stars in thestars were declared successful in participating in the second cycle of learning activities, thus 13 children out of 15 children were declared successful because they had shown success in improving vocabulary skills through the field trip method (rice fields). Children are already able to appear in front of the class by saying clear vocabulary and reading writing and do not need to continue in the next cycle. Keywords: Early Childhood; Vocabulary Skills; Ende Language; Field Trip Methods